2015
DOI: 10.1111/inr.12218
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' pain assessment practices with critically ill adult patients

Abstract: Interventions to reduce barriers and enhance enablers of acute pain assessment are needed to improve pain management in critically ill adult patients. To be effective, the interventions have to be holistic and implemented by professional bodies and employers of nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 40 publications
(86 reference statements)
2
38
3
Order By: Relevance
“…Critically ill patients may suffer from a multitude of neurological, physiological and communicative disabilities arising from a variety of reasons, which may be further complicated by intubation and use of sedatives (Kizza & Muliira, 2015). Inappropriate diagnosis and management of acute pain may lead to increased morbidity and mortality (Auvray, Myin, & Spence, 2010; Lord & Varndell, 2019; Schug, Palmer, Scott, Halliwell, & Trinca, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Critically ill patients may suffer from a multitude of neurological, physiological and communicative disabilities arising from a variety of reasons, which may be further complicated by intubation and use of sedatives (Kizza & Muliira, 2015). Inappropriate diagnosis and management of acute pain may lead to increased morbidity and mortality (Auvray, Myin, & Spence, 2010; Lord & Varndell, 2019; Schug, Palmer, Scott, Halliwell, & Trinca, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, acute pain was identified as the most frequently used nursing diagnoses in the SICU and CVICU. This result is reasonable because critically ill patients admitted to the ICU experience significant pain due to reasons related to their disease, surgery, and routine care such as turning and suctioning (Kizza & Muliira, ; Stites & Surprise, ). However, degree centrality revealed a difference between the two units.…”
Section: Discussionmentioning
confidence: 99%
“…According to the reported results, only a small number of nurses provide appropriate care when the patient is experiencing pain. However, they have a moral responsibility to provide the best clinical care in pain relief (25). The nurses' awareness and attitude play an important role in the implementation of an effective pain management process (26) and the results of previous studies showed that training programs in the field of pain significantly enhance the nurses' knowledge and attitude toward pain (27,28).…”
Section: Introductionmentioning
confidence: 99%